Erythropoietin mediates brain-vascular-kidney crosstalk and may be a treatment target for pulmonary and resistant essential hypertension - Emine Meltem Onal; Alan Alper Sag; Oguzhan Sal; Aslihan Yerlikaya; Baris Afsar; Mehmet Kanbay (Clinical and Experimental Hypertension, 2017)
Organ crosstalk pathways represent the next frontier for target-mining in molecular medicine for existing syndromes. Pulmonary hypertension and resistant essential hypertension are syndromes that have been proven elusive in etiology, and frequently refractory to first-line management. Underlying crosstalk mechanisms, not yet considered in these treatments, may hinder outcomes or unlock novel treatments. This review focuses systematically on erythropoietin, a synthesizable molecule, as a mediator of brain-kidney crosstalk. Insights gained from this review will be applied to cardiovascular diseases in a clinician-directed fashion.